PENYULUHAN PENGATURAN KONSUMSI MAKANAN SEHAT DAN PEMERIKSAAN GLUKOSA DARAH DI KELOMPOK POSYANDU LANSIA RW 18 PERUMNAS MOJOSONGO, SURAKARTA, JAWA TENGAH - Rizal Maarif Rukmana; Dewi Sulistyawati; Ratna Herawati (LP4MK STKIP PGRI Lubuklinggau, 2019)
Unbalanced and irregular diet can lead to a variety of degenerative diseases. Foods that are high in carbohydrates, fats, and proteins will increase blood glucose levels in the body. Increased blood glucose will trigger diabetes mellitus. The purpose of this community service is to provide information and knowledge about regulating healthy eating patterns for the elderly and measuring blood glucose levels. Counseling with oral presentation methods and direct communication methods. The method for determined blood glucose levels is by using a rapid test. The results showed that the provision of counseling regulating healthy food consumption had a positive impact as indicated by the decrease in blood glucose levels in the elderly Posyandu community in Rw 18 Perumnas Mojosongo, Surakarta, Central Java, before counseling and after counseling.